EWSR1:YY1 fusion positive peritoneal epithelioid mesothelioma harbors mesothelioma epigenetic signature: Report of 3 cases in support of an emerging entity. Issue 10 (24th June 2022) - Dermawan, Josephine K.; Torrence, Dianne; Lee, Cheng‐Han; Villafania, Liliana; Mullaney, Kerry A.; DiNapoli, Sara; Sukhadia, Purvil; Benayed, Ryma; Borsu, Laetitia; Agaram, Narasimhan P.; Nash, Garrett M.; Dickson, Brendan C.; et al.
Abstract: Mesothelioma is a rare, aggressive malignant neoplasm of mesothelial origin. A small subset of peritoneal mesothelioma is driven by recurrent gene fusions, mostly EWSR1/FUS::ATF1 fusions, with predilection for young adults. To date, only two cases of mesothelioma harboring EWSR1::YY1 fusions have been described. We present three additional cases of EWSR1::YY1‐ fused peritoneal mesotheliomas, two localized and one diffuse, all occurring in the peritoneum of middle‐aged adults (2 females and 1 male), and discovered incidentally by imaging or during surgery performed for unrelated reasons. None presented with symptoms or had a known history of asbestos exposure. All three cases were cellular epithelioid neoplasms with heterogeneous architectural patterns comprising mostly solid nests and sheets with variably papillary and trabecular areas against collagenous stroma. Cytologically, the cells were monomorphic, polygonal, epithelioid cells with dense eosinophilic cytoplasm and centrally located nuclei. Overt mitotic activity or tumor necrosis was absent. All cases showed strong diffuse immunoreactivity for pancytokeratin, CK7, and nuclear WT1, patchy to negative calretinin, retained BAP1 expression, and were negative for Ber‐EP4 and MOC31. RNA‐sequencing confirmed in‐frame gene fusion transcripts involving EWSR1 exon 7/8 and YY1 exon 2/3. By unsupervised clustering analysis, the methylation profiles of EWSR1::YY1 ‐fused mesotheliomas clustered similarly with EWSR1/FUS::ATF1 ‐fused mesotheliomas and conventional mesotheliomas, suggesting a mesothelioma epigenetic signature. All three patients underwent surgical resection or cytoreductive surgery of the masses. On follow‐up imaging, no recurrence or progression of disease was identified. Our findings suggest that EWSR1::YY1‐ fusion defines a small subset of peritoneal epithelioid mesothelioma in middle‐aged adults without history of asbestos exposure.